PENGARUH EFIKASI DIRI DAN KEPUASAN KERJA TERHADAP KINERJA ‎GURU MELALUI BUDAYA OCB DI KORWIL DINAS PENDIDIKAN ‎KECAMATAN SEDAN ‎ - Mushlahul Halim (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2020)
This research is done by the authors because there are still many problems in the Education Office of Rembang regency, including the low efficacy and morale of teachers in Rembang Regency. This research uses quantitative research, which is a process of finding knowledge using numbers as a tool to analyze what you want to know and to draw conclusions using statistical calculations. The variables used in this study are the dependent variable (teacher performance), the independent variable (self-efficacy and job satisfaction) and the intermediate variable (work motivation). From this research, the researcher concludes that self-efficacy and motivation affect teacher performance in Rembang Regency. Self-efficacy has a positive and significant effect on the OCB culture of teacher performance, so that hypothesis 1 (H1) is accepted and Hypothesis zero (H0) is rejected. Job satisfaction has a positive and significant effect on O, so that hypothesis 2 is accepted and hypothesis 0 is rejected. Self-efficacy has a positive and significant effect on performance, so hypothesis 3 is proven and hypothesis zero is rejected. Job satisfaction has a positive and significant effect on performance, so that hypothesis 4 is proven and the null hypothesis (H0) is rejected. The influence of work OCB culture on performance. OCB has a positive and significant effect on performance, so that hypothesis 5 is proven. Based on the results of the F test of equation II, it is concluded that together the independent variables (self-efficacy, OCB and job satisfaction) have a positive and significant effect on the dependent variable (teacher performance).Keywords: self-efficacy, job satisfaction, OCB culture teacher performance